GAMBARAN PERFORMA DOKTER UMUM DAN DOKTER SPESIALIS SEBAGAI INSTRUKTUR SKILLS LAB DI FAKULTAS KEDOKTERAN UNIVERSITAS PATTIMURA - lidya Bethsi Evangeline Saptenno (PAMERI, 2023)
Introduction: Skills lab is a means for pre-clinical students to learn and practice clinical skills. In the learning process, an instructor is needed who is responsible for facilitating the mentoring process. Those who act as skills lab instructors at the Faculty of Medicine, University of Pattimura are general practitioners and specialist doctors. To support their role, an instructor needs basic knowledge and skills in providing clinical skills training. This research was conducted to describe the performance of skills lab instructors at the Faculty of Medicine, Pattimura University. Method: This research is a quantitative descriptive study using a questionnaire that has been adopted from the "Instrument for Evaluating Clinical Skills lab Teacher's Dictactil Performance" questionnaire, which has been tested for validity and reliability. This questionnaire consists of 26 indicators covering three aspects, namely teaching skills, interpersonal skills and communication skills, as well as skills training conditions/strategies. Respondents as many as 140 students were selected purposively, namely students in class III and IV because they had passed most of the stages of preclinical education and training in almost all Skills lab modules. The data is then analyzed descriptively. Results: Almost all indicators on the three aspects of Skills lab instructor performance, get an accumulated good and very good rating of more than 70% of students. The aspect of teaching skills had the highest accumulation on the 8th indicator, namely 97.1% (136 students) for general practitioners and 97.9% for specialist doctors. The 3rd indicator on interpersonal and communication aspects, got the highest accumulation of 92.9% (130 students) for general practitioners and 91.4% (128 students for specialist doctors. Finally, the 4th indicator on the condition/training strategy aspect skills got the highest accumulation of 93.6% (131 students) for general practitioners and 99.3% (139 students) for specialist doctors. Conclusion: In general, the performance of general practitioners and specialists as Skills lab instructors at the Faculty of Medicine, University of Pattimura was described as good by students, with several indicators that were still considered lacking and required further evaluation.